Sentinel lymph nodes biopsy in the surgical treatment of endometrial cancer: history and present - M. O. Ochirov (Opuholi Ženskoj Reproduktivnoj Sistemy, 2019)
This article reviews the concept of sentinel lymph node biopsy in patients with endometrial cancer. This technique is becoming increasingly appreciated and was included into the latest standards of surgical treatment for gynecological cancers. Sentinel lymph node mapping is a reliable and highly specific (100 %) method, which can be used for determining the indications for adjuvant therapy in addition to a detailed pathomorphological examination that should include immunohistochemical testing and ultrastaging.